"Do not Disturb the Peace!" Identities, Livelihoods and the Politics of Post-War Discontent in Sierra Leone. (June 2019) - Batty, Fodei; M'Cormack-Hale, Fredline
Although the collective memory of war is frequently invoked in post-war societies, who chooses to invoke it and to what effect has been less studied relative to other aspects of such societies. In this article we employ a case study of Sierra Leone to address this deficit in the post-conflict scholarship by illustrating how the collective memory of that country's civil war is appropriated by diverse actors in the post-war society. Drawing from field interviews, we present evidence showing how, and why, several societal groups constituted as distinct post-war identities such as victims-rights groups, former defenders of the state, or perpetrators of the violence during the Sierra Leone civil war articulate dissatisfactions with their livelihoods and the reactions of state officials to their demands. The article explains why, and how, successive governments have selectively suppressed the discontent of some groups over livelihood insecurities that are construed as threats to public order while ignoring violent protests from other groups over similar issues, in spite of a 1965 public order act restricting protests. Thus, the article argues that state officials in Sierra Leone have not demonstrated superior commitment to peacebuilding than societal groups that make demands on the state.